MANAGEMENT OF THE EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) APPLICATION IN DECISION MAKING AT MI DDI 1 PALOPO - Putriani Putriani; Rosdiana Rosdiana; Alimuddin Alimuddin; N Akbar N Akbar; Firmansyah Firmansyah (Media Inovasi Pendidikan dan Publikasi, 2026)
This article discusses the management of the Education Management Information System (EMIS) application in decision-making at MI DDI 1 Palopo. This research is motivated by the importance of utilizing information technology to support systematic and accurate educational data management for precise decision-making by the madrasah principal. The objectives of this research are to identify the implementation process of the EMIS application in decision-making and its impacts at MI DDI 1 Palopo. This study employs a qualitative approach with a descriptive research type. Data collection techniques include observation, interviews, and documentation studies using primary and secondary data sources. Research subjects consist of the madrasah principal and EMIS operator. Data were analyzed using the interactive model by Miles, Huberman, and Saldana, encompassing data collection, data reduction, data presentation, and conclusion drawing. The results indicate that EMIS implementation runs effectively through processes of data collection, inputting, analysis, verification, and utilization of data on students, teachers, curriculum, and facilities, which serve as the basis for decisions such as class arrangements, teacher task assignments, scheduling, budgeting, and aid applications. The use of EMIS provides positive impacts in the form of faster, more accurate, and centralized data management compared to manual methods, thereby supporting relevant data-based decisions.